국내 베트남 결혼이민여성과 한국인 배우자의 식이섭취 및 식습관에 대한 상관관계 - 김선혜(Sun Hye Kim); 김화영(Wha Young Kim); 유지은(Ji Eun Lyu); 정혜원(Hye Won Chung); 황지윤(Ji Yun Hwang) (Korean journal of community nutrition, 2009)
This study aimed to examine nutritional status and similarities of diets between Vietnamese female immigrants and Korean spouses and dietary changes of Vietnamese females after immigration. Subjects were 608 couples visiting 13 medical centers for the Cohort of Intermarried Women in Korea from November 2006 to November 2007. Anthropometric and biochemical measurements were obtained and dietary intakes were assessed using one-day 24-hour recall. Sixty-eight percent of wives answered there have been changes in their diets and consumptions of meats, fish, dairy products, vegetables, and fruits increased after immigration. Energy intakes of wives and spouses were 1491.7 kcal and 1788.8 kcal, respectively, showing most couples (80.1%) consumed less than the Korean estimated energy requirements. More than half of the couples were below the Korean estimated average requirements of zinc, vitamin $B_2$, and folate. The correlation coefficients between couples ranged 0.15-0.38 for unadjusted, 0.22-0.35 for per 1000 kcal, and 0.21-0.40 for energy-adjusted, respectively. The proportions of couples in the same quartiles of each nutrient intake and in the same answers of each question of Mini Dietary Assessment were about 30% across nutrients and around 50% across questions. The length of residence is related to similarities of nutrient intakes between couples: similarities decreased after 3 years of residence in Korea. In conclusion, nutritional intakes of inter-married couples were inadequate although wives reported that their dietary intakes increased after immigration. Inadequate nutrient intakes of wives were partly explained by similar diets between couples because these wives without enough adjustment to Korean culture were more likely to follow what their spouses ate. Findings from this study may be helpful to improve the nutritional status of inter-married couples and make policies and programs for them. A follow-up study should identify factors affecting inadequate nutritional status of intermarried couples and similarities of their diets.